Creatively prototyping the future high street. Issue 6 (25th April 2016) - Fletcher, Gordon; Greenhill, Anita; Griffiths, Marie; Holmes, Kate; McLean, Rachel
Abstract: This paper gives a voice to a range of community and individual stakeholders who would not generally be heard in the conventional town planning process. We present a methodological technique, described as creative prototyping, that has at its heart, the capability to enable full stakeholder inclusivity into the future imagining of the smart city. Actively involving these individuals and community representatives in the research process enables deeper understanding of how technology and people can interact productively to create smart cities that are socially inclusive while still being commercially relevant. The research data for this paper are drawn from the findings of a workshop conducted by the authors that utilised Science Fiction Prototyping and Lego Serious Play . This research activity was driven by questions focusing upon the current complex interplay and tensions of technology and the UK's physical high street. We first explore these issues theoretically in previous literature and then drawn upon this review to analyse the outcomes of the workshop. Three themes emerge from this analysis that have operational and strategic relevance to the development of future high streets; the importance of ever present but invisible technology, the forefronting of people in the smart city and the need for wide-ranging stakeholder input and participation into planning. The findings also illustrate that not all future imaginings of the retail high street are immediately practical or realistically applicable. However, in examining the many issues facing the current high street and in negotiating the multiplicity of voices with their competing demands and expectations, we offer the conclusion that the future smart city must become a place of truly shared sociality – rather than just mere proximity, customised convenience or a concentration point for multiple forms of entertainment.